Modified citrus pectin confers a preventative effect on cancer-related pathways in CdCl2-treated C. elegans - Shi, Denia Cai; Hotchkiss, Arland T.; Lawton, Michael A.; Di, Rong (Food hydrocolloids for health, 2023)
Cadmium chloride (CdCl2) is a toxic compound found as a pollutant in the environment due to agricultural and industrial sources. Exposure to Cd2+ is known to promote malignant tumors such as lung cancer and leukemia. While the current medications for cadmium toxicity focus on treatments to promote the excretion from the body, treatments to improve health after cadmium exposure are less well studied. Modified citrus pectin (MCP) is a polysaccharide derived from citrus peels that has been shown to induce natural killer cell activity in myeloid leukemia cells and also act as a natural chelation agent to help excrete toxic metals from healthy human subjects. We hypothesized that MCP might have a counteracting effect against CdCl2 toxicity through cancer-related pathways. This study investigates the effects of MCP on CdCl2 toxicity in C. elegans, which shares a number of cancer-related pathways with mammals. The results indicated that MCP was able to significantly counter the toxic effects of CdCl2 on C. elegans lifespan and development. Our studies suggest that the beneficial effects of MCP may result from its ability to mitigate the effects of CdCl2 on gene expression, particularly in conserved pathways associated with apoptosis, tumor induction and suppression and inflammation-related pathways.